2019
DOI: 10.1063/1.5092629
|View full text |Cite
|
Sign up to set email alerts
|

A complex network theory analytical approach to power system cascading failure—From a cyber-physical perspective

Abstract: The modern electric power grid is evolving rapidly into such a state that distributed controllers and two-way energy and information flow are replacing the traditional paradigm of electricity distribution and energy management. Therefore, a power grid coupled with a communication network is playing a pivotal role in establishing modern electric power systems. Previous cascading failure analysis in power systems focused more on the physical network, while falling short of investigations on the coupling effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…The coupling relationship between the communication layer nodes and physical layer nodes in the CPPS system is the basis of the interaction between the communication space and physical grid. The coupling relationship changes dynamically with the operation state of the CPPS system [9], [38]- [41]. On one hand, the function and shape of CPPS system nodes are different; thus, there are many connection types, such as one-way tight coupling, one-way loose coupling, and two-way loose coupling.…”
Section: ) Coupling Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling relationship between the communication layer nodes and physical layer nodes in the CPPS system is the basis of the interaction between the communication space and physical grid. The coupling relationship changes dynamically with the operation state of the CPPS system [9], [38]- [41]. On one hand, the function and shape of CPPS system nodes are different; thus, there are many connection types, such as one-way tight coupling, one-way loose coupling, and two-way loose coupling.…”
Section: ) Coupling Relationshipmentioning
confidence: 99%
“…represents the set of nodes at the physical layer that can be detected by the scheduling center and meets the following requirements: (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) According to the information received, the dispatching center takes the minimum load loss as the objective function to carry out an optimization calculation and defines SC(P The dispatching center updates the electrical parameters to the working nodes of the communication layer along with the control instruction. A control information transmission failure occurs when the transmission delay is greater than the threshold MaxT , and the node receiving the control information adjusts the electrical properties according to P j∼ 12 .…”
Section: ) Physical Layer Failure Analysismentioning
confidence: 99%
“…(19), (21) and classical measure in Eq. (6), (7), four parameters and the vulnerability of three communities are shown in Table 1.…”
Section: An Illustrative Examplementioning
confidence: 99%
“…">IntroductionRecently, cyber-physical system (CPS) has attracted much attention in numerous fields, such as microgrid [1], smart city [2], internet of things [3,4], and so on. Meanwhile, how to model CPS into specific physical models to analyze their performance and property has become the focus of research [5].Therefore, complex network has been applied in this field to better understand the performance of CPS [6,7], because nodes in the network represent individuals in the system, and edges would show the relationship between these individuals. Most of previous researches focus on the structure and topological property, which can quantify the characteristic and performance of network.…”
mentioning
confidence: 99%
“…Similarly, a CPS-based review of models and methodologies for smart grids can be found in [18]. Complex network theory provides a powerful tool in modelling the different CPS layers and their interactions, e.g., they can be used to analyze the effects of cyberattacks or how cascading failures progress from the cyber to the physical layer and vice versa [8,19]. Cyberattacks result in compromised measurement signals from sensors or control signals from actuators, e.g., via communication package losses, creating the need for attack-resilient power systems through the development of novel cybersecurity methods and technologies [20,21].…”
Section: Introductionmentioning
confidence: 99%